White Lupin as a Promising Source of Antioxidant Phenolics for Functional Food Production - Alena Vollmannova; Judita Lidikova; Janette Musilova; Marek Snirc; Tatiana Bojnanska; Dana Urminska; Ivana Tirdilova; Erika Zetochova (Journal of Food Quality)
Although white lupin is the oldest known legume in the history, it has been forgotten for many years. Now, the interest of food producers concerning white lupin is increased again. The aim of this study was to evaluate the total phenolic content (TPC), antioxidant activity (AA), and the content of selected phenolics in 11 white lupin cultivars. The determined TPC was in the interval 4260–5663 mg GAE/kg DM and the values of AA determined using DPPH•, ABTS•+, and FRAP methods were in the ranges 0.993–1.878, 5.496–7.924, and 1.328–1.741 μmol TE/g DM, respectively. Individual phenolics content (4-hydroxybenzoic acid, caffeic acid, trans-p-coumaric acid, trans-ferulic acid, myricetin, quercetin, apigenin, and genistein) were determined, too. Caffeic acid (442.9–766.2 mg/kg DM) and myricetin (11.2–21.2 mg/kg DM) are the dominant phenolics in the investigated lupin cultivars. Statistically significant differences in all investigated variables were observed between the tested cultivars except for quercetin. The obtained results show that the Astra and Nelly cultivars are a rich source of phenolic acids.